Cybersecurity Career Profiling (Journal of The Colloquium for Information Systems Security Education, 2017)
Professionalization of a cybersecurity workforce is under development from multiple perspectives. Government agencies, the military and academic institutions strive to standardize excellent curriculum and career pathways, certifications, job descriptions classifications are contributing to the effort. In its infancy is the development of statistically validated psychological profiles of candidates' possessing the talent, disposition and interest to excel in the rapidly maturing field and diversifying field of cybersecurity. To address this gap we propose to borrow from the well- established medical profession and utilize psychological profiling protocols tailoring a statistically validated career assessment tool to build cybersecurity psychological profiles of two markedly different cybersecurity career pathways. Once profiles are defined and validated we propose several Next Steps. Team members and industry partners comparing the psychological profiles can advise or refute a case to conduct additional profiling of additional cybersecurity career pathways. The assessment protocols and methodology will be disseminated to multiple communities at regional, national and international conferences to increase the diversity and numbers of talent entering the cybersecurity career pipeline.